Integrative multi-omics analysis identifies FAM3D as a prognostic tumor suppressor in cervical cancer - Yanbin Chen; Yu Hong; Dongjun Wei; Lianjiao Fan; Dian Tao; Rui Zhang; Hongwei Yang (Functional & Integrative Genomics, 2026)

A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

TROAP aggravates chemoresistance of colorectal cancer cells via lipogenesis by PI3K/Akt pathway and histone acetylation - Ling-Ling Wang; Rui Zhang; Ning Li; Zheng-Guo Cui; Hua-Chuan Zheng (Functional & Integrative Genomics, 2025)

CLDN4 promotes ferroptosis and inflammation involving JAK2/STAT3 pathway in acute pancreatitis - Chuanming Zheng; Rui Tao; Zhenjie Wang; Xi Zhang; Hai Jiang; Zhong Ji; Hehe Dou; Zhaohui Du (Functional & Integrative Genomics, 2025)

MZB1-Driven Endoplasmic reticulum stress model as a predictor of breast cancer progression and survival - Purong Zhang; Rui Wang; Yuying Wang; Ning Zhang; Ke Luo (Functional & Integrative Genomics, 2025)

Comparative pan-genome analysis of Huperzia and Phlegmariurus and transcriptomics reveals thermal adaptation in Huperzia - Muzi Li; Yazhu Wu; Haibo Li; Zhongnian Zhang; Rui Qin; Jiahao Wen; Yeqin Xu; Chengcheng Bao; Dekai Wang (Functional & Integrative Genomics, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Pan-omics insights into abiotic stress responses: bridging functional genomics and precision crop breeding - Tayachew Admas; Shu Jiao; Rui Pan; Wenying Zhang (Functional & Integrative Genomics, 2025)

Dynamic cellular composition and immune landscape revealed by single-cell transcriptome profiling in a brain arteriovenous malformation - Yutong Liu; Hongchuan Niu; Junze Zhang; Rui Liang; Zhenyu Zhou; Chengxu Lei; Shihao He; Changyu Lu; Yuanli Zhao (Functional & Integrative Genomics, 2025)

Circular RNA circ_0022707 impedes the progression of preeclampsia via the miR-3135b/GHR/PI3K/Akt axis - Huijing Shao; Rui Guan; Zixi Chen; Ruijiao Kong; Caihong Zhang; Hang Gu (Functional & Integrative Genomics, 2024)

Genome-wide identification and expression-pattern analysis of sulfate transporter (SULTR) gene family in cotton under multiple abiotic stresses and fiber development - Yu Chen; Xianghui Xiao; Rui Yang; Zhihao Sun; Shuhan Yang; Haibo Zhang; Baoguang Xing; Yanfang Li; Qiankun Liu; Quanwei Lu; Yuzhen Shi; Youlu Yuan; et al. (Functional & Integrative Genomics, 2024)

Epidemiology, pathogenesis, immune evasion mechanism and vaccine development of porcine Deltacoronavirus - Xueting Shan; Rui Li; Xiang Ma; Guoqiang Qiu; Yi Xiang; Xiaojun Zhang; De Wu; Lu Wang; Jianhong Zhang; Tao Wang; Weifen Li; Yun Xiang; et al. (Functional & Integrative Genomics, 2024)

TRIM5 as a promising diagnostic biomarker of hepatocellular carcinoma: integrated analysis and experimental validation - Huanxiang Liu; Yuhong Tang; Jiahao Zhang; Gefeng Wu; Qing Peng; Chen Chen; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Guoqing Jiang; Qian Wang; et al. (Functional & Integrative Genomics, 2024)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

Resveratrol plays an anti-fibrotic and anti-autophagy role by stimulating miR-192-5p expression in urethral fibrosis - Jin Lv; Rui Zhang; DaoYuan Li; Yan Liu (Functional & Integrative Genomics, 2023)

Comparative analysis of mitochondrial genomes provides insights into the mechanisms underlying an S-type cytoplasmic male sterility (CMS) system in wheat (Triticum aestivum L.) - Rui Wang; Qingsong Ba; Lanlan Zhang; Weilun Wang; Pengfei Zhang; Guiping Li (Functional & Integrative Genomics, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Validation of reliable safe harbor locus for efficient porcine transgenesis - Xiang Ma; Weijun Zeng; Lei Wang; Rui Cheng; Zeying Zhao; Caiyun Huang; Zhongxin Sun; Peipei Tao; Tao Wang; Jufang Zhang; Lu Liu; Xing Duan; et al. (Functional & Integrative Genomics, 2022)

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

C2CD4A/B variants in the predisposition of lung cancer in the Chinese Han population - Feifei Han; Lu Qian; Yi Zhang; Ping Liu; Rui Li; Mingwei Chen (Functional & Integrative Genomics, 2022)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Systematic analysis of lncRNA expression profiles and atherosclerosis-associated lncRNA-mRNA network revealing functional lncRNAs in carotid atherosclerotic rabbit models - Yingnan Wu; Feng Zhang; Xiaoying Li; Wenying Hou; Shuang Zhang; Yanan Feng; Rui Lu; Yu Ding; Litao Sun (Functional & Integrative Genomics, 2020)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)